Development of a science literacy-based e-module for elementary school students - Rani Ardianti; Putri Octa Hadiyanti (Inovasi Kurikulum, 2025)
Students’ understanding of science concepts often encounters difficulties due to their abstract nature, including the topic of the respiratory system, which impacts students’ low interest in learning and their science literacy skills. To overcome these challenges, innovative, communicative, and child-friendly learning media are needed. This study aims to develop a science literacy-based e-module on the respiratory system that can serve as an alternative medium for science learning among fifth-grade elementary school students. The research method employed was a research and development approach, utilizing the ADDIE model, with a primary focus on the development stage. The research subjects consisted of a material expert, a language expert, a media expert, one teacher, and six students in a limited trial. Data collection instruments included validation sheets and response questionnaires. The analysis technique employed a descriptive approach, utilizing both qualitative and quantitative methods. The results showed that the developed science literacy-based e-module is feasible for use in learning. Teachers and students provided positive responses, stating that the e-module helped explain the concept of the respiratory system more clearly, systematically, and understandably. Thus, the science literacy-based e-module on the respiratory system is considered effective as a learning medium that supports the strengthening of science literacy while enhancing students’ understanding of scientific concepts in elementary school.   Abstrak Pemahaman murid terhadap materi sains seringkali menghadapi kendala karena sifatnya yang abstrak, termasuk pada materi sistem pernapasan, sehingga berdampak pada rendahnya minat belajar dan keterampilan literasi sains murid. Untuk mengatasi permasalahan tersebut, diperlukan media pembelajaran yang inovatif, komunikatif, dan sesuai dengan karakteristik anak. Penelitian ini bertujuan mengembangkan e-modul berbasis literasi sains pada materi sistem pernapasan yang dapat digunakan sebagai media alternatif dalam pembelajaran IPA di kelas V sekolah dasar. Metode penelitian yang digunakan adalah penelitian dan pengembangan dengan model ADDIE yang dibatasi sampai tahap pengembangan. Subjek penelitian terdiri atas ahli materi, ahli bahasa, ahli media, seorang guru, serta enam murid pada uji coba terbatas. Instrumen pengumpulan data berupa lembar validasi dan angket respons, sedangkan teknik analisis dilakukan secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa e-modul berbasis literasi sains yang dikembangkan layak digunakan dalam pembelajaran. Guru dan murid memberikan respons positif karena e-modul ini membantu menjelaskan konsep sistem pernapasan secara lebih jelas, sistematis, dan mudah dipahami. Dengan demikian, e-modul berbasis literasi sains pada materi sistem pernapasan dinyatakan efektif sebagai salah satu media pembelajaran yang mendukung penguatan literasi sains sekaligus meningkatkan pemahaman murid terhadap konsep-konsep sains di sekolah dasar. Kata Kunci: e-modul; literasi sains; sekolah dasar